Transport policies in Hungary - historical background and current practice for national and regional level - Vilmos Oszter (European Transport Research Review, 2017)
Abstract Introduction This paper presents an overview of the current and past evolution of the Hungarian Transport Policies and investigates how and what kind of results could be used in the future transport concepts and strategies. It also examines the practice of coordination between the different territorial and administrative levels of transport planning. It aims to identify the applied policy instruments and the monitoring processes installed. Methods By using literature and legal background review from the past and current plans and policies the paper will also share the author’s own empirical work experience while participating in the elaboration of the New National Transport Strategy (NKS) as well as an insight from the Transport Policy for Budapest (Balázs Mór Plan). It gives an overview about the recent changes in the Transport Policy of Hungary and its implication for the project priority lists. Results The expected results are the clear identification of synergies and gaps among the ongoing policies together with the divulgation of good and bad practices for the wider professional audience. Conclusions The need for a sustainable transport system, which assumes a sustainable economy as well is a huge challenge for policy makers. In order to avoid parallel policy making (especially when making policies for different areas) and minimize the economic and social cost of transport, we need a coordinated, multimodal approach, which includes the necessary organizations and public private bodies (with secure and sustainable financial background) with exact tasks and responsibility on all territorial levels.